Key internal determinants of share price of commercial banks in Malaysia / Zainal Abidin Jailani - Jailani, Zainal Abidin (Faculty of Business Management, 2014)
Commercial banks play a vital role in the economic resource allocation of countries. They channel funds from depositors to investors continuously. Good financial performance rewards the shareholders for their investment. This paper is to measure the impact of key internal determinants in commercial bank in Malaysia towards their share price. Many researchers have made a research for this study but they have produced contradictory results and therefore have failed to give conclusive results. From this study, portfolios managers, investors and also the customer of the bank may find results in this research useful for determining the future behavior and performance of stock prices, for identifying investment approaches, pursuing available investment opportunities, and reducing the probability of high value losses in the market. A selected journals and articles will be review for this study so it can be help in completing this research paper objective. The data for this study will be found from reliable sources and from the data, several empirical test will be perform whether its meet this paper objectives which is to measure the impact of key internal determinants of commercial bank in Malaysia towards their share price or not.